Human dimensions of forest landscape restoration - Mansourian, Stephanie; Derkyi, Mercy; Djenontin, Ida; Elias, Marlène; Oldekop, Johan; Pacheco, Pablo; Burns, Janice; Diederichsen, Anita; Kleine, Michael; Vallauri, Daniel; Walder, Bethanie (2024)
Forest landscape restoration (FLR) is a human affair. As with all ecosystem restoration approaches, in FLR humans are part of the social-ecological system within which restoration activities take place: what people do in the landscape directly affects all components of a natural ecosystem such as soil, vegetation including forest, faunal diversity and vice versa. It is therefore, essential to understand and include the human dimensions of FLR at all stages of planning, implementation and monitoring. Although there have been some attempts to do so, most of the attention has centred on the ecological aspects of the forested landscape with limited attention to the human system. And as the UN Decade on Ecosystem Restoration is driving even greater investments in FLR and other ecosystem restoration approaches, there is an urgent need to improve the ways that human dimensions are considered in all ecosystem restoration efforts.